ECONOMIC ANALYSIS OF THE ELECTRONIZATION OF JUDICIAL ENFORCEMENT IN HUNGARY - Udvary, Sandor (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The article reviews the fundamental economic analysis of law issues regarding civil procedure, then proves their applicability in the field of judicial enforcement procedure. The author formulates the equation for the rational decision maker for initiating enforcement procedure and also analyzes the elements of that equation. He identifies the costs as key issue to the efficiency of the procedure and presents those rules with economic analysis. Then he turns to the electronization of the Hungarian enforcement procedure, which resulted in great increase in efficiency. Electronic means of communication, electronic attachment and auction shall be reviewed and evaluated from the economic point of view. His conclusions – beyond demonstrating the validity of economic analysis on this field – show that electronization of judicial enforcement provides an increase in social efficiency.
Keywords: economic analysis of law, judicial enforcement procedure, economic analysis of judicial enforcement, electronization of judicial enforcement, efficiency of judicial enforcement